APPOINTMENT OF MARRIAGE GUARDIANS IN MUALLAF MARRIAGES IN KARO REGENCY (COMPARATIVE ANALYSIS OF THE VIEWS OF KUA KABANJAHE AND KUA BERASTAGI) - Noto Wibowo; Zainul Fuad; Syafruddin Syam (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Marriage is a method developed by Allah as a strategy to preserve the life of the people of the prophet Muhammad, one of the main pillars of marriage is a bride's guardian. This research is analyzed with the legal research method of empiricism, it’s empirical analysis of the ijtihad method of the Chief of Religious Affairs  of Kabanjahe District and  Berastagi District, Karo Regency, addressing the case of the appointment of a guardian in the marriage of a female Muslim convert , with a sociological and anthropological approach and Gustav Radbruch's theory of law enforcement, namely legal certainty, justice and expediency.  The method of the Head of Religious Affairs of Kabanjahe Subdistrict in determining the marriage guardian of a muallaf is First; paying attention to the religion of the father of the bride, if he is Muslim then he has the right to become a guardian regardless of his previous religious background, Second; if he is not Muslim, then a search for his descendants who are Muslim because the head of the Kabanjahe sub-district religious affairs prioritizes the guardian of the lineage. Third; if a search has been made from the side of relatives and there are none, then the judge's guardian acts as a guardian in the marriage, However, according to the Head of the Kabanjahe Religious Affairs Office, the third point rarely occurs in Kabanjahe, because the Kabanjahe community is majority Karo, identical  with Rakut Si Telu culture, which is very moderate in religion. As for the Berastagi religious affairs office, the determination of the marriage guardian is carried out by paying attention to three stages of analysis, namely; First; by paying attention to the context, namely the muallaf whether he is a muallaf from parents who have long been muallaf' or only he is a new muallaf and his parents are still non-Muslim. Secondly, by taking into account the marriage system of the parents, whether the marriage of the parents was carried out in a Christian marriage, Islam or just a customary marriage, then if it was not previously Islamic, then, Thirdly, the legal and entitled guardian of the judge.